KEY FACTORS FOR REDUCING LIVE POULTRY LOSSES DURING TRANSPORTATION - Valery KURGANOV; Mikhail GRYAZNOV; Egor TIMOFEEV; Liliya POLYAKOVA (Scientific Journal of Silesian University of Technology. Series Transport, 2021)
The results of this study on the loss of live poultry at various stages of delivery from the farm to the processing plant by road are given. A factor analysis of the reasons for the loss of livestock delivered from the farm to the processing plant was carried out. The dependencies of livestock losses on loading delays and the duration of the movement of the loaded poultry farm to the processing plant were established. Methodological recommendations for rationing the number of injuries observed during delivery were developed. The study of losses of live birds during delivery to the processing plant from the density of stocking in shipping boxes was carried out; the economic and mathematical model for optimizing the landing of live birds in shipping boxes was proposed. The calculation of the economic impact of the implementation of the results of the study is given.